Stabilized β-Catenin Ameliorates ALPS-Like Symptoms of B6/lpr Mice. (9th November 2017) - Xu, Xiaoxie; Huang, Jun; Zhao, Mei; Chen, Huanpeng; Mo, Jinhua; Zhou, Xiaoqing; Su, Qiao; Yu, Bolan; Huang, Zhaofeng
Abstract : Autoimmune lymphoproliferative syndrome (ALPS) is an incurable disease mainly caused by the defect of Fas-mediated apoptosis and characterized by nonmalignant autoimmune lymphoproliferation. Stabilized β -catenin could not only potentiate Fas-mediated T cell apoptosis via upregulating the expression of Fas on activated T cells, but also potentiate T cell apoptosis via intrinsic apoptotic pathway. In the present study, we introduced β -cat Tg into lpr / lpr mice and aimed to explore the potential role of stabilized β -catenin ( β -cat Tg ) in the development of ALPS-like phenotypes of lpr / lpr mice. We found that the total splenocyte cells and some compositions were slightly downregulated in β -cat Tg lpr / lpr mice, especially the CD4 and CD8 TEM cells were significantly reduced. Meanwhile, stabilized β -catenin obviously decreased the numbers of spleen TCR β + CD4 − CD8 − T (DNT) cells, and the levels of some serum proinflammatory factors also were lowered in β -cat Tg lpr / lpr mice. Beyond that, stabilized β -catenin slightly lowered the levels of the serum autoantibodies and the scores of kidney histopathology of β -cat Tg lpr / lpr mice compared with lpr / lpr mice. Our study suggested that stabilized β -catenin ameliorated some ALPS-like symptoms of lpr / lpr mice by potentiating Fas-independent signal-mediated T cell apoptosis, which might uncover a potential novel therapeutic direction for ALPS.